Central European Countries’ Competition Law Practice Contribution to the Development of EU Competition Law - Tóth, András (The Policies of the European Union from a Central European Perspective, 2022)
The case law of the Central European EU Member States has made important contributions to the development of EU competition law through preliminary rulings. First, restriction of competition ‘by object’ is an open category since the European Court of Justice’s judgment in the Hungarian insurance cartel: the competition authority or the court may also declare market conduct as anti-competitive by object if it is not yet characterized as having an anti-competitive object. Second, preliminary ruling questions referred from Central European countries have given the EU Court of Justice an opportunity to clarify the relationship between national and EU competition law.Keywords: EU competition law, restriction competition by object, ne bis in idem, parallel applicability of EU and national competition law